The predictors and determinants of inter-seasonal success in a professional soccer team - Kite, C. S.; Nevill, A. (Journal of Human Kinetics, 2017)
The aims of this study were to 1) directly compare the performances of a professional soccer team over three seasons, 2) identify key variables that discriminated between a successful or unsuccessful performance, and 3) identify variables that best predicted success. ANOVA revealed that attempted and completed passes were significantly lower (both p < 0.001) in the most successful season (S1). Additionally, shot effectiveness was significantly less (p < 0.001) in their least successful season (S3) (vs S1 -11.61%; d = 0.735; vs S2 -12.02%; d = 0.760). When the match outcome was considered, they attempted significantly fewer passes when they won (-60.26; p = 0.002; d = -0.729) or drew (-44.87; p = 0.023; d = -0.543) compared to when they lost. The binary logistic regression analysis also retained passing variables. The team should attempt fewer passes, but ensure that more of these passes are completed. With away matches, the effect became more pronounced (ß = -0.042, OR = 0.959, p = 0.012). In conclusion, the team should adopt a more direct style of play. They should move the ball into a shooting position with fewer passes and ensure that more shots are on the target.